PERAN PEKERJA SOSIAL TERHADAP ANAK BERHADAPAN DENGAN HUKUM DI BALAI REHABILITASI SOSIAL ANAK MEMERLUKAN PERLINDUNGAN KHUSUS (BRSAMPK) - Ilham Supiana; Juliana Juliana; Gilang Susalit (JSSHA ADPERTISI JOURNAL, 2022)
The purpose of this study was to obtain an overview of the duties or functions of social workers as advocates, counselors and educators in the social rehabilitation of children dealing with the law at BRSAMPK Toddopuli Makassar. The type of research used is descriptive with a qualitative approach. Data collection techniques, the primary data is done by structured and semi-structured interviews while the secondary data is by library research. The results of the study found that the role of social workers as advocates is one of the roles that is often used by social workers at the Toddopuli Children's Social Rehabilitation Center (BRSAMPK) to provide assistance to children who are in conflict with the law in court proceedings starting from preparing all children's social reports. and referrals if possible the child has other needs. The role of social workers as educators for children dealing with the law at the Toddopuli social rehabilitation center for children requiring special protection (BRSAMPK), namely providing education both knowledge and skills for empowering children, conducting supervision, compiling educational activities. The role of social workers as counselors for children dealing with the law is in the social rehabilitation center for children requiring special protection (BRSAMPK) Toddopuli, namely providing motivation to children, helping children to be responsible in solving or facing problems, providing suggestions and solutions to children so that children can immediately solve problems , formulate or discuss problems or conduct case conferences if the social worker does not find a solution to a child's problem.